Modern approaches to complex therapy of chronic nonspecific endometritis (review of literature) - V. V. Bochkov; A. N. Plekhanov (Acta Biomedica Scientifica, 2015)
The article presents the review of modern Russian and foreign literature devoted to a problem of treatment of chronic endometritis. It was shown that treatment of this pathology should be conducted in two stages. The basis of the first stage is antibacterial therapy, the basis of the second stage is complex treatment with application of vascular preparations, vitamin therapy, endocrinotherapy, physiotherapy. In addition the article brings up several debatable questions of treatment of chronic endometritis and expediency of application of hormones, probiotic, immunomodulators in particular. Also the article presents the estimation of various methods of medical products introduction. The positive effect is received from local application of medical products. It was noticed that the search of new medical products is proceeding.